Reduction of Steel Corrosion Rate Using Natural Inhibitor from Cocoa Pod Husk Extract in HCl Solution - Prameswari, Apriska; Asmar Putra, Iqbal Kurniawan; Putra, David Eka (Universitas PGRI Palembang, 2025)
This study explores the effectiveness of cocoa husk extract as a natural corrosion inhibitor for steel exposed to hydrochloric acid (HCl). Steel samples were immersed in the extract solution for four different durations: 48, 96, 144, and 192 hours. After coating, the samples were subjected to an HCl solution for 168 hours. The corrosion rate was assessed using the weight loss method, which quantifies mass reduction as an indicator of corrosion severity. Surface characteristics were analyzed through optical microscopy, Scanning Electron Microscopy (SEM), and theoretical modeling using Density Functional Theory (DFT). The findings demonstrate that the application of cocoa husk extract significantly reduces corrosion rates, with a maximum inhibition efficiency of 78.4%. This improvement is attributed to the formation of a protective layer on the steel surface, which acts as a barrier against acid interaction. The results suggest that cocoa husk extract is a promising, environmentally friendly alternative for protecting steel materials from corrosion.